CONTRADICTIONS OF THE MISDEMEANOR LAW IN THE AREA OF SANCTIONS FOR MINORS, WITH SPECIAL REVIEW TO THE MEASURES THAT ARE OF MEDICAL CHARACTER - Samardžić, Stefan; Milić, Ivan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Minors represent a special category of offenders, due to the age at the time of commission of a misdemeanor. Hence, the law prescribes special sanctions for them. A special attention has been given to measures that are of medical character. However, the Law on Misdemeanors has contradictory provisions in terms of sanctions for minors by differentiating, in certain provisions, between younger and older minors. In the first part, this paper deals in general with offenders of misdemeanors that are minors, while sanctions are dealt with in the second part of the paper. Central part of the paper deals with the issues surrounding protective measure “Mandatory treatment of alcohol and psychoactive substance addicts”, by pointing to some irrational provisions of the Law. In relations to that issue, the paper discuss whether in certain situations the law is more harsh on minors that commit misdemeanor offences or minors that commit criminal offences, having in mind prescribed sanctions.